Voluntary Export Restraints on Automobiles: Evaluating a Trade Policy - Berry, Steven; Levinsohn, James; Pakes, Ariel (American Economic Review, 1999)
We evaluate the voluntary export restraint (VER) that was initially placed on exports of automobiles from Japan in 1981. We evaluate the impact this policy had on U.S. consumer welfare, firm profits, and forgone tariff revenue from its initiation through 1990. (JEL F13)